Red Dawn : HISK Laureates 2014. - Sandqvist, Gertrud (Gent : HISK / Hoger Instituut voor Schone Kunsten, 2014)
Bosmans, Kasper ; Doms, Liesbeth ; Ramm Fortun, Marthe ; Galiazzo, Andrea ; Lamas, Nicolas ; Lasurt Bachs, Lola ; Monko, Marge ; Pelzer, Nicolas ; Undo, Katerina ; Vanheerswynghels, Birde
boek